Rights Fulfillment of Children From Mixed Marriages to Obtain Indonesian Citizenship Based on Law Number 12 of 2006 - Kukoh Iqbal; Siti Hasanah; Firzhal Arzhi Jiwantara; Nurjannah Septyanun (Universitas Muhammadiyah Palu, 2025)
This research aims to analyze the regulation and implementation of fulfilling the rights of children from mixed marriages to obtain Indonesian citizenship based on Law Number 12 of 2006. Normative-empirical research with legislative, conceptual and sociological approaches in qualitative descriptive analysis. Data used are primary, secondary and literature research materials and field research. The conclusions are; First, Law Number 12 of 2006 grants limited dual citizenship status to children born from mixed marriages after its enactment on August 1, 2006. However, to ensure legal certainty, children born from mixed marriages before the law was enacted are required to register themselves. Second, the terminology 'child with dual citizenship' in the Law implies that if another country, based on its regulations, recognizes a child from a mixed marriage as its citizen, then they fall under this category. Meanwhile, there isn't any country that explicitly, based on its provisions, does not recognize children from mixed marriages as its citizens. Third, the process of fulfilling the citizenship rights of children born from mixed marriages is burdened upon the individual concerned. Consequently, any negligence in administrative processes, requirements, and procedures can lead to the loss of Indonesian citizenship. Fourth, the implications of losing Indonesian citizenship for children from mixed marriages can have legal and sociological impacts.